Selected clinico-morphological and immunohistochemical criteria for prognosis of small cell lung cancer - Yakovtsova , I.I.; Yanchevskyi , O.V. (Морфологія / Morphologia / Morfologìâ, 2022)
Background. Small cell lung cancer (SCLC) is one of the most aggressive histological forms of lung cancer. It requires combined radiation and chemotherapy at an early stage of the tumour process. Determination of immunohistochemical (IHC) criteria for the clinical course of SCLC is critical for individualized patient treatment tactics. Objective. Improvement of the morphological criteria for the prognosis of the course of SCRL based on the study of clinical-morphological and molecular-biological characteristics of primary tumours. Methods. Surgically removed SCLC and deceased patients’ autopsies were selected. Formed research groups: I localized SCLC (LD-SCLC) and II extensive-stage (ES-SCLC). The period from the moment of diagnosis to the death of the patients was taken into account. IHC study of primary tumours was performed with the determination of the expression of markers: Ki-67, CD56, synaptophysin, pan cytokeratin, vimentin and CD44. Results. It was found that the level of proliferative activity of ES-SCLC is lower than the level of LD-SCLC (p<0.001). A direct statistically significant relationship between the survival time and the level of expression of Ki-67 was determined, which characterizes the Ki-67 marker as a criterion for a favourable prognosis of SCLC. A correlational dependence was found to a shorter overall survival (OS) of patients on SCLC among cases with positive expression of vimentin (p<0.001). The appearance of IHC evidence of the processes of epithelial-mesenchymal transformation of SCRL is accompanied by a tendency to the appearance of a stem-like immunophenotype of cancer cells and a partial loss of the neuroendocrine status of the tumour.